Peran Humas UIN Ar-Raniry dalam Membangun Relasi dengan Media Pers - Nazarullah (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2021)
This study attempts to describe the communication strategies used and various kinds of activities carried out by UIN Ar-Raniry public relations in establishing relationships with the press media. The research method used in this study is the qualitative method with a descriptive approach. The data sources of this study were obtained from respondents as the primary data source through several stages in the form of observations records, in-depth interviews, and documentation. The data analysis was performed by using descriptive qualitative analysis techniques through three flows of activities that were carried out simultaneously, namely data reduction, data presentation, and conclusion drawing. The result of the study revealed that the role of public relations of UIN Ar-Raniry in establishing relations with the press media has been going well. It can be seen from the communication strategies used and the various forms of activities that is organized by UIN Ar-Raniry public relation in developing relations with the press media. The communication strategy used is a two-way symmetrical and Reciprocity communication strategy that conforms to the principles of media relations. Several kinds of activities carried out by UIN Ar-Raniry public relations in developing relationships with the press media are Press Coverage, Press Conference, Press Release, Press Statement, Press Interview, and Electronics Communications. Meanwhile, the informal activities are Press Reception and Morning Coffee.